Written expression in boys with ADHD: The mediating roles of working memory and oral expression. Issue 6 (18th August 2019) - Eckrich, Samuel J.; Rapport, Mark D.; Calub, Catrina A.; Friedman, Lauren M.
ABSTRACT: The written expression difficulties experienced by children with ADHD are widely recognized; however, scant empirical evidence exists concerning the cognitive mechanisms and processes underlying these deficiencies. The current study investigated the independent and potentially interactive contributions of two developmentally antecedent cognitive processes – viz., working memory (WM) and oral expression – hypothesized to influence written expression ability in boys. Thirty-three boys with ADHD-Combined Presentation and 27 neurotypical (NT) boys 8–12 years of age were administered standardized measures of oral and written expression, and multiple counterbalanced tasks to assess WM central executive (CE) processes, WM phonological short-term memory (PH STM), and WM visuospatial short-term memory (VS STM). Bias-corrected bootstrapped mediation analyses revealed a significant mediation effect, wherein the independent and interactive effects of PH STM and oral expression collectively explained 76% of the diagnostic status to written expression relation. The implications of the obtained results for clinical practice suggest that children with ADHD may benefit by incorporating a blended approach that simultaneously strengthens PH STM capacity and oral expression abilities as antecedents to engaging in writing-related activities.